The Impact of Tacrolimus on Vascular Endothelial Growth Factor in Experimental Corneal Neovascularization - Turgut, Burak; Guler, Mete; Akpolat, Nusret; Demir, Tamer; Celiker, Ulku (Taylor & Francis Inc, 2011)
Purpose: To investigate the impact of tacrolimus on vascular endothelial growth factor (VEGF) in experimental corneal neovascularization (NV) immunohistochemically. Material and Methods: Five groups of seven Wistar albino rats were formed. A silver nitrate cauterization technique was used to induce corneal NV in the study groups, excluding Group 1 (Control Group). Rats in group 1 did not receive any treatment. Rats in group 2 (sham 1) were administered 1 ml of saline intraperitoneally once a day and those in group 3 (sham 2) received one drop of saline four times a day. Rats in group 4 were administered 0.3 mg/kg tacrolimus intraperitoneally once a day. For group 5, 0.3 mg/ml tacrolimus was installed four times a day. Digital photography for each cornea was performed and the percentage area of the NV on the total corneal surface was calculated. The intensity of VEGF immunostaining in the epithelial, the stromal, and endothelial layers was performed in a semi quantitative fashion. Results: The mean percentages of the neovascularized areas of intraperitoneally and topically tacrolimus-treated groups were lesser than those of the sham groups (p = 0.002, p = 0.038, respectively). The mean intensity of the epithelial VEGF immunostaining of the intraperitoneally tacrolimus-treated group was less than that of its sham group (p = 0.002), while the mean intensity of the stromal VEGF staining of the topically tacrolimus-treated group was lesser than that of its sham group (p = 0.042). The intensities of the endothelial VEGF immunostaining of the intraperitoneally and topically tacrolimus-treated groups were less than those of the sham groups (p = 0.038, p = 0.032). Conclusion: Systemic and topical administration of tacrolimus may be beneficial in the prevention of corneal NV because of its effect on VEGF.
Keywords: Corneal neovascularization; Tacrolimus; VEGF